Pluripotent stem cells secrete Activin A to improve their epiblast competency after injection into recipient embryos. Issue 8 (12th October 2017) - Xiang, Jinzhu; Cao, Suying; Zhong, Liang; Wang, Hanning; Pei, Yangli; Wei, Qingqing; Wen, Bingqiang; Mu, Haiyuan; Zhang, Shaopeng; Yue, Liang; Yue, Genhua; Lim, Bing; et al.
Abstract: It is not fully clear why there is a higher contribution of pluripotent stem cells (PSCs) to the chimera produced by injection of PSCs into 4-cell or 8-cell stage embryos compared with blastocyst injection. Here, we show that not only embryonic stem cells (ESCs) but also induced pluripotent stem cells (iPSCs) can generate F0 nearly 100% donor cell-derived mice by 4-cell stage embryo injection, and the approach has a "dose effect". Through an analysis of the PSC-secreted proteins, Activin A was found to impede epiblast (EPI) lineage development while promoting trophectoderm (TE) differentiation, resulting in replacement of the EPI lineage of host embryos with PSCs. Interestingly, the injection of ESCs into blastocysts cultured with Activin A (cultured from 4-cell stage to early blastocyst at E3.5) could increase the contribution of ESCs to the chimera. The results indicated that PSCs secrete protein Activin A to improve their EPI competency after injection into recipient embryos through influencing the development of mouse early embryos. This result is useful for optimizing the chimera production system and for a deep understanding of PSCs effects on early embryo development.